Encapsulation of Hibiscus sabdariffa Extract into Zein Nanoparticles. Issue 10 (31st August 2020) - Calliari, Caroline Maria; Campardelli, Roberta; Pettinato, Margherita; Perego, Patrizia
Abstract: A combined approach for the extraction of antioxidants from Hibiscus sabdariffa and entrapment of the extract in zein nanoparticles is proposed. Different green extraction techniques were adopted: high‐pressure and ‐temperature extraction, ultrasound‐assisted extraction, and microwave‐assisted extraction, using an ethanol/water mixture as extracting solvent. The extracts were used for the preparation of zein nanoparticles by liquid antisolvent precipitation. The impacts of process variables were investigated using response surface modeling, demonstrating that the proposed strategy allows high extract encapsulation efficiency, good particle size control, and high particle stability. Abstract : Antioxidant‐rich extracts from Hibiscus sabdariffa were encapsulated by the antisolvent precipitation process, and zein particles with high entrapment efficiency and nanometric size were obtained. Response surface modeling was used to optimize the process variables. The Hibiscus extract in the zein nanoparticles exhibited good stability for 3 months.